Fungicides and insecticides efficiency on wheat and triticale - Baier, Augusto Carlos (Pesquisa Agropecuaria Brasileira, 2014)
The fungicides and insecticides efficiency for control of wheat (Triticum aestivum L.) and triticale (Triticasecale Wittmack) diseases and aphids was tested during three years. The chemical action of these pesticides on yield, test weight, degradation of green leaf area, incidence of septoria, scab, leaf rust, mildew, aphids and leaf yellowing is demonstrated. During rainy years, like 1977 and 1979, a high fungicidal efficiency in controlling diseases, slowing leaf degradation, and increasing yield and test weight was observed in wheat and triticale. The highest yield increases were obtained in both crops when diseases and aphids were controlled simultaneously. Test weight was increased from 1 to 7 kg per hectoliter. In triticale, duo to the pesticides, more than the minimum of 65 kg/hl was obtained. Significant yield increases, doe to the fungicide treatment prior heading, were lower in triticale. In the favorable year of 1978, the fungicide treatment after heading did not increase yield.
Keywords: pesticides; fungus diseases; aphids; leaf blight disease